Design and implementation of an astrophotography image processing app on mobile phone - Ishida Kris (Nanyang Technological University, 2022)
Astrophotography involves the documentation of celestial events, astronomical objects such as the moon and the night sky. It also includes the visual recording of the constellation and planets. It is known for its complexity and requires an in-depth understanding of the use of equipment and photography techniques. Due to extreme low light in astrophotography environments, post-processing is necessary for improving the signal-to-noise ratio in images. Stacking multiple images is a popular method of creating stacked images, which is achieved by aligning and averaging pixels together.